Snap-through Buckling of Shallow Spherical Shells under Ring Loads - Karatas, Esra Eylem; Yukseler, Receb Faruk (TURKISH CHAMBER CIVIL ENGINEERS, 2021)
Snap-through buckling behaviour of rigid vinyl polyethylene shallow spherical shells, undergoing large displacements, subjected to static ring loads is investigated by using finite difference and the Newton-Raphson Method. The load-deflection diagrams corresponding to various values of thickness, depth and ring diameter of the shell with simply supported and clamped edges are sketched and compared. The accuracy of the used algorithm and the prepared computer program are tested by comparing some of the numerical results obtained in this study with those obtained by an experimental study, available in the relevant literature. Further steps on the concerning subject are achieved.
Keywords: Shallow spherical shell; nonlinear behaviour; large deflection; snap-through buckling; upper-limit point; rigid vinyl polyethylene; stability; GEOMETRICALLY NONLINEAR-ANALYSIS; RUBBER-LIKE SHELLS; ARCHES; BEHAVIOR; Engineering